Households Sociodemographic Profile as Predictors of Health Insurance Uptake and Service Utilization: A Cross-Sectional Study in a Municipality of Ghana. (14th March 2018) - Badu, Eric; Agyei-Baffour, Peter; Ofori Acheampong, Isaac; Preprah Opoku, Maxwell; Addai-Donkor, Kwasi
Abstract : Introduction. Attempts to use health insurance in Low and Middle Income Countries (LMICs) are recognized as a powerful tool in achieving Universal Health Coverage (UHC). However, continuous enrolment onto health insurance schemes and utilization of healthcare in these countries remain problematic due to varying factors. Empirical evidence on the influence of household sociodemographic factors on enrolment and subsequent utilization of healthcare is rare. This paper sought to examine how household profile influences the National Health Insurance Scheme (NHIS) status and use of healthcare in a municipality of Ghana. Methods. A cross-sectional design with quantitative methods was conducted among a total of 380 respondents, selected through a multistage cluster sampling. Data were collected using a semistructured questionnaire. Data were analysed using descriptive and multiple logistics regression at 95% CI using STATA 14. Results. Overall, 57.9% of respondents were males, and average age was 34 years. Households' profiles such as age, gender, education, marital status, ethnicity, and religion were key predictors of NHIS active membership. Compared with other age groups, 38–47 years (AOR 0.06) and 58 years and above (AOR = 0.01), widow, divorced families, Muslims, and minority ethnic groups were less likely to have NHIS active membership. However, females (AOR = 3.92), married couples (AOR = 48.9), and people educated at tertiary level consistently had their NHIS active. Proximate factors such as education, marital status, place of residence, and NHIS status were predictors of healthcare utilization. Conclusion. The study concludes that households' proximate factors influence the uptake of NHIS policy and subsequent utilization of healthcare. Vulnerable population such as elderly, minority ethnic, and religious groups were less likely to renew their NHIS policy. The NHIS policy should revise the exemption bracket to wholly cover vulnerable groups such as minority ethnic and religious groups and elderly people at retiring age of 60 years.